Social Interaction and Collaboration among Oncology Nurses - Jane Moore; Dawn Prentice; Maurene McQuestion (Nursing Research and Practice)
Collaboration is a complex process influenced by organizational, professional, interpersonal, and personal factors. Research has demonstrated that collaboration may also be influenced by social factors. Nurses spend much of their time working in collaborative teams, yet little is known about how they socially interact in practice. This qualitative case study explored nurse perceptions of social interaction in relation to collaboration. Data were collected using telephone interviews and documentary reviews from fourteen oncology nurses employed at one cancer center in Canada. Thematic analysis revealed two themes: knowing you is trusting you and formal and informal opportunities. Nurses reported that social interaction meant getting to know someone personally as well as professionally. Social interaction was enacted inside of work during breaks/meals and outside of work at planned events. Social interaction was facilitated by having a long-term current and/or previous professional and personal relationship. The barriers to social interaction included a lack of time to get to know each other, workload issues, and poor interpersonal skills. Findings suggest that social interaction is an important factor in the collaborative relationship among oncology nurses. Nurse leaders need to promote social interaction opportunities and facilitate educational sessions to improve social and interpersonal skills.